Property tax incentives for preservation : use-value assessment and the preservation of farmland, open space, and historic sites - Property Tax Forum ( 1975 : Washington); International Association of Assessing Officers. Research and Technical Services Dept. ([s.l] : International Association of Assessing Officers, 1975)
36